2016
DOI: 10.1002/cpt.446
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Design for a Confirmatory Basket Trial in Multiple Tumor Types Based on a Putative Predictive Biomarker

Abstract: Increasingly, tumors are defined on a molecular basis rather than only on histology, and targeted agents, which address these molecular subtypes, are being approved. This profusion of molecular subtypes creates "rare" diseases as subsets of common cancers, leading to difficulties in enrolling sufficiently large cohorts for confirmatory trials. However, if the molecular subtype is shared across various histologies, these may be pooled into a basket trial. To date, basket trials have been primarily for explorato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
80
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 33 publications
0
80
0
Order By: Relevance
“…Basket designs can be viewed as an extension of the biomarker enrichment design. In contrast to the biomarker enrichment design that follows a prespecified selection (or de‐selection) sequence of its subpopulations based on the biomarker levels, the basket design selects or deselects subpopulations based on their tissue of origin (or other indications for nononcology applications) without any requirement on the ordering sequence of the subpopulations.…”
Section: Basket Designmentioning
confidence: 99%
“…Basket designs can be viewed as an extension of the biomarker enrichment design. In contrast to the biomarker enrichment design that follows a prespecified selection (or de‐selection) sequence of its subpopulations based on the biomarker levels, the basket design selects or deselects subpopulations based on their tissue of origin (or other indications for nononcology applications) without any requirement on the ordering sequence of the subpopulations.…”
Section: Basket Designmentioning
confidence: 99%
“…Because the interpretation of genomic test results is becoming increasingly complex and time intensive, personalized medicine consultation services are beginning to emerge. These services have the goal of identifying drugs or clinical trials for which the patient is eligible based on reported actionable mutations . Most genomic‐targeted chemotherapeutic agents have on‐label indications listed in the FDA drug insert Indications and Usage section that identifies the somatic mutation and cancer type for which the drug is approved.…”
mentioning
confidence: 99%
“…Other examples include off‐label use of olaparib in nonovarian BRCA ‐mutated cancers . Novel clinical trial designs, such as basket trials, are exploring the clinical utility of targeting molecular alternations independent of tumor type …”
mentioning
confidence: 99%
See 2 more Smart Citations